2012
DOI: 10.1109/tbme.2012.2210716
|View full text |Cite
|
Sign up to set email alerts
|

Simple Patient-Based Transmantle Pressure and Shear Estimate From Cine Phase-Contrast MRI in Cerebral Aqueduct

Abstract: From measurements of the oscillating flux of the cerebrospinal fluid (CSF) in the aqueduct of Sylvius, we elaborate a patient-based methodology for transmantle pressure (TRP) and shear evaluation. High-resolution anatomical magnetic resonance imaging first permits a precise 3-D anatomical digitalized reconstruction of the Sylvius's aqueduct shape. From this, a very fast approximate numerical flow computation, nevertheless consistent with analytical predictions, is developed. Our approach includes the main cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…The existence of pulsatile pressure gradients has been hypothesized–as indeed suggested by the cardiac and respiratory CSF flow cycles. ICP differences in the cerebral aqueduct have been estimated from PC-MRI flow measurements 24,25 . However, very few have studied pulsatile ICP gradients clinically and directly 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of pulsatile pressure gradients has been hypothesized–as indeed suggested by the cardiac and respiratory CSF flow cycles. ICP differences in the cerebral aqueduct have been estimated from PC-MRI flow measurements 24,25 . However, very few have studied pulsatile ICP gradients clinically and directly 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, from computational studies it is well-known that the magnitude of CSF pressure gradients is only a small fraction of the ICP pulsation (typically >5 mmHg during a cardiac cycle) 2 . For example, a 42 μ L aqueductal stroke volume was estimated to correspond to an approximately 0.01 mmHg pressure drop in both a rigid and a deformable normally shaped patient-specific geometry 26 , while other computational studies have estimated a transmantle pressure difference of up to 0.03 mmHg 24,27 . Severely stenosed aqueducts may however have pressure drops that are orders of magnitude higher 28 .…”
Section: Introductionmentioning
confidence: 99%
“…This normalization depends not only on the section plane on the PC MRI but also on a high-resolution anatomical magnetic resonance imaging that permits a precise 3-D anatomical digitalized reconstruction of the entire Sylvius aqueduct. Then, an approximate numerical flow can be computed to measure the flow resistance and thus, calculate the pressure gradient between the 3rd and 4th ventricle [23]. …”
Section: Discussionmentioning
confidence: 99%
“…A typical characteristic of communicating hydrocephalus is high pulsatile CSF flow [35], and experimental studies have hinted at a causal link between altered CSF pulsations and ventricular enlargement [68]. Since the largest pressure changes in the ventricular system occur over the CA [9, 10], it is reasonable that altered pulsatile flow dynamics over the CA could play a part in the development of ventriculomegaly in these patients. Looking at the flow through the CA, it can be observed that it is asymmetric, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…CFD also allows us to take the entire CA geometry into account, which is problematic to do analytically. Previous CFD studies have presented data on the pressure differences over the CA in hydrocephalus case studies and in healthy [9, 10, 17, 18], but to fully determine its magnitude and potential role in communicating hydrocephalus a study specifically designed to investigate the transmantle pressure gradient in a larger group of communicating hydrocephalus patients is needed, utilizing the highest quality imaging data feasible.…”
Section: Introductionmentioning
confidence: 99%